2010
DOI: 10.1007/s00127-010-0317-9
|View full text |Cite
|
Sign up to set email alerts
|

The natural course and outcome of major depressive disorder in primary care: the PREDICT-NL study

Abstract: PurposeTo examine the natural course and outcome of major depressive disorder (MDD) in primary care over 39 months.MethodsProspective cohort study of 1,338 consecutive attendees with follow-up after 6, 12, and 39 months with DSM-IV MDD using the Composite International Diagnostic Interview (CIDI). We measured severity of depressive symptoms (Patient Health Questionnaire 9), somatic symptoms (Patient Health Questionnaire 15), and mental and physical function (Short Form 12, mental and physical component summary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 35 publications
6
58
3
5
Order By: Relevance
“…11,15 The long-term prognosis of depression and anxiety is generally poor, with a substantial proportion of patients not recovering and with many recurrences; the initial severity is an important predictor. [16][17][18][19][20][21][22][23] Regarding the long-term presentation of depression in general practice, it has been reported that about 40% of patients have a recurrence of depression in general practice within a 10-year period. 24, 25 Lloyd et al 26 found relapses or chronic psychiatric conditions after 11 years in one-third of those included with neurotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…11,15 The long-term prognosis of depression and anxiety is generally poor, with a substantial proportion of patients not recovering and with many recurrences; the initial severity is an important predictor. [16][17][18][19][20][21][22][23] Regarding the long-term presentation of depression in general practice, it has been reported that about 40% of patients have a recurrence of depression in general practice within a 10-year period. 24, 25 Lloyd et al 26 found relapses or chronic psychiatric conditions after 11 years in one-third of those included with neurotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…8 The accuracy of family physicians in predicting the course of depression is described as fair, 9 although as in other conditions it has been studied relatively little. Useful predictors of poor depression outcome in primary care have been identified in 3 main areas: individual characteristics (age, 10 high neuroticism levels, 11 perceived need for care, 12 low mastery 13 ); socioeconomic status (low education level, 12 low income, 12 unemployment 12 ); loneliness, 12 low social support, 12,14 limitations of social activities due to health 14 ; and health, both physical (medical comorbidity, 11,12,14,15 chronic pain, 11 daily smoking 13 ) and mental (comorbid anxiGilles Ambresin, MD 1 ety, 11,12,15 double depression, 11 severity of depressive symptoms, 11,12,14,16 somatic symptoms of depression, 16 history of recurrent depression, 15 remission status at 3 months, 15 appropriate use of antidepressant medications, 14 greater mental dysfunction 16 ). Reliable assessment of the predictors listed above requires time and a multitude of validated instruments.…”
mentioning
confidence: 99%
“…También se detectó una frecuencia de riesgo suicida superior a 70%, cifra cercana a la reportada en hospitales comunitarios de la X región 24 , pero más alta que la señalada en el extranjero [31][32] . Estos indicadores de compromiso del cuadro clínico son predictores de mala respuesta y recurrencia/cronicidad 27,28,33,34 , y parecieran influirse recíprocamente en pacientes depresivos de APS 31,32 .…”
Section: Discussionunclassified